THERAPEUTIC PHYSICAL FACTORS IN THE COMPLEX REHABILITATION OF PATIENTS WITH HYPERTENSION (LECTURE) - Марцияш, Алексей Алексеевич; Елгина, Светлана Ивановна; Рудаева, Елена Владимировна; Мозес, Кира Борисовна; Ласточкина, Лилия Алексеевна; Фомина, Наталья Викторовна; Черных, Наталья Степановна; Солдатова, Наталья Владимировна (Medicine in Kuzbass, 2024)
Diseases of the cardiovascular system are a medical and social problem of great importance in all industrialized countries of the world. Hypertension (GB), along with coronary heart disease, occupies a leading position in terms of the growth rate of morbidity, prevalence, disability and mortality of the population. Thus, the prevalence of arterial hypertension (AH) among the adult population is 30-45 %, with age the incidence increases to 60-70 % in people 65 years and older. In this regard, the issues of organizing and improving the prevention, treatment and rehabilitation of patients with hypertension seem relevant, which, in turn, is noted in the state program for combating cardiovascular diseases. The main goal of rehabilitation of patients with hypertension is to reduce the risk of developing cardiovascular complications, social integration, and physical factors play a key role in this.